Will Increasing Residential Density Decrease Parking Availability? A Method for Practitioners. - Dave Amos (Findings)
Cities in the United States aim to increase the supply of affordable housing in low-density areas, but residents are concerned about the availability of parking as density increases. This study measures on- and off-street parking vacancy in three neighborhoods zoned single-family "R-1" and three zoned moderate-density "R-2" to understand if increasing housing density reduces parking vacancy. Results indicate that while there is more vacancy in R-1 neighborhoods, the R-2 neighborhoods still have significant excess capacity. Furthermore, the method for finding this result is low-cost and potentially useful to local planners interested in increasing residential density while addressing local concerns.